Bibliometric analysis on human capital training and education / Siti Hajar Samsu and Nelson Lajuni - Samsu, Siti Hajar; Lajuni, Nelson (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
A workforce, so called human capital is an asset to the country, organization and company. An effective investment in human capital can be seen in the development of innovation, productivity and competitiveness o f a country. Therefore, most countries human capital investment is done through training and education. It is believed that sustainable human capital investment in training and education is important to ensure a high economic growth and development. Thus, the objective of this study is to perform bibliometric analysis on scientific literature published in the field of human capital training and education. Scopus database was used to gather all related literature on human capital training and education. Apart from employing SPSS and Microsoft Excel software, we also utilize Publish or Perish software to integrate the data and perform a simple analysis before using VOS viewer to perform data visualization. Publications growth, the productivity of research and citation analysis were reported via standard bibliometric analysis. A total of 1,218 documents were retrieved based on the keyword search results and excluded. The study of human capital training and education began 53 years ago, to be exact since 1968. Most articles were written in English and published in journals and conferences articles. Majority of these articles were in the Business, Management and Accounting fields. The bibliometric analysis presents the advancement of the scientific literature on human capital training and education and highlights the area of interest that future researchers should explore.